Influence of deviatoric stress on rockburst occurrence: An experimental study - Thomas Bruning; Murat Karakus; Selahattin Akdag; Giang D. Nguyen; David Goodchild (International Journal of Mining Science and Technology, 2018)
As mining delves deeper into the crust, it is necessary to investigate the complex rock responses associated with higher stress gradients. Therefore, it is essential to better understand the mechanisms associated with the rockburst phenomenon. However, due to the large-scale and difficult monitoring of real mining excavations, laboratory scale tests must be utilised to determine the conditions conducive to burst. To this end, this research focuses on the implementation of a new rockburst testing apparatus to replicate the stress conditions of a rock mass excavation at the time of bursting. This apparatus allows the determination of rockburst stresses and a relationship between deviatoric stress and in-situ pressure/depth. Using this relationship it is then possible to estimate the standardised stress levels for a certain rock type which might lead to rockburst occurrence. Furthermore, it is demonstrated that with increasing in-situ pressure, the likelihood (measured as a lower differential stress) and the extent (indicated by the increasing range of deviatoric stress) of rockburst increases. These findings provide valuable information about the conditions necessary for bursting in deep mining. Keywords: Rockburst test, Hollow cylinder, Hard rock, In-situ stress